Model and Characteristics of Micro Finance Institutions Based on SME Women in Batu City - Ike Kusdyah Rachmawati (University of Islam Malang, 2017)
The development of SMEs is largely determined by the existence of MFIs that offer financing models are diverse. It can be said that MFIs become a partner of SMEs in this regard as a financial services provider, through diverse financing models. But on the other hand the diversity of financing models offered by MFIs have not been fully able to be utilizedThis study used exploratory research, descriptive, experimental and applied research conducted in stages for the development of a comprehensive model of microfinance accommodative Informants determined based on the information needs. Using a descriptive and qualitative analysis of the MFI deliberately selected examples illustrate the following: (A) The existence of MFIs is recognized community has a strategic role as an intermediary in economic activity that has not affordable public services of banking institutions / conventional banks; (B) service MFIs have demonstrated success, but success can still be in business economics. Skim MFI lending to businesses has not received the priority, it is characterized by a relatively small ceiling (budget allocation) to support farming, which is less than 10% of the total ceiling of MFIs; (C) A critical factor in the development of the agricultural sector MFI lies in the institutional legality, capability management, seed capital support, the economic viability of farming, farm characteristics and technical assistance clients / service users MFIs; (D) To initiate the growth and development of agricultural MFIs needed guidance enhanced capabilities for HR candidates MFI managers, support the strengthening of capital and technical assistance to customers of credit users.Keywords: Financial Institutions Micro, Small Business Micro